A Crocodile for Billy - Chris Rhodes (London Lady Birds Books, 2020)
Billy really really wants a Crocodile, more than anything in the world. But how will he ever afford one? Especially when there are so many other exciting things to buy. Join Billy in this delightful tale about a little boy with a big plan...
Keywords: EY - RM -- EY - RM